Characterization of UF foulants and fouling mechanisms when applying low in-line coagulant pre-treatment. (1st December 2017) - Peleato, Nicolas M.; Legge, Raymond L.; Andrews, Robert C.
Abstract: Fluorescence spectroscopy was used as a characterization method to examine organic fouling of single ultrafiltration (UF) fibres at bench-scale. Low doses of coagulant were applied to modify organic properties, without significant formation of precipitates. This approach compliments previous studies investigating coagulation as a pre-treatment method for UF fouling control, which have principally focused on reduction of foulant concentrations. Using a continuous system, short time-scale fluorescence results demonstrated significant adsorption of humic components to virgin membrane fibres. Following an initial adsorption phase, protein-like material was the only organic component to be significantly removed by UF. Low doses of coagulant (<1 mg/L as alum; < 0.043 mg/L as Al 3+ ) were observed to significantly reduce irreversible fouling rates for two different surface waters. Paralleling reduced irreversible fouling, surface tryptophan fluorescence resulting from material adsorbed to the fouled membrane increased, as measured using a fibre optic probe. Analysis of peak shifts in the protein-like component revealed a red-shift at low coagulant dose, possibly indicative of greater exposure of tryptophan residues resulting from conformational changes in the protein structure. It is hypothesized that low coagulant doses modified membrane-foulant interactions, resulting in increased adsorption of protein-like matter to the surface. Subsequent interactions of bulk foulants with the adsorbed organic monolayer discouraged further adsorption and reduced irreversible fouling potential. Graphical abstract: Image 1 Highlights: Low in-line doses of coagulant were applied to alter organic character. Irreversible fouling rates decreased from low alum doses (<0.043 mg/L Al 3+ ). Novel fibre optic fluorescence surface scans of fouled membranes. Increased surface protein adsorption associated with reduced irreversible fouling. Protein peak shifts suggest conformational changes from low alum doses.